Comparison of a laboratory-developed test targeting the envelope gene with three nucleic acid amplification tests for detection of SARS-CoV-2 (2020)
Background Numerous nucleic acid amplification tests, including real-time, reverse transcription PCR (rRT-PCR) and isothermal amplification methods, have been developed to detect SARS-CoV-2 RNA, including many that have received emergency use authorization (EUA). There is a need to assess their test performance relative to one another. Objectives The aim of this study was to compare the test performance of a high complexity laboratory-developed rRT-PCR EUA from Stanford Health Care (SHC) targeting the SARS-CoV-2 envelope (E) gene with other tests: the Atila isothermal amplification assay targeting the nucleocapsid (N) gene and open reading frame 1ab (ORF1ab), the Altona E and spike (S) multiplex, real-time RT-PCR, and the US Centers for Disease Control and Prevention (CDC) N1 and N2 rRT-PCRs. Study Design A diagnostic comparison study was performed by testing nasopharyngeal samples from persons under investigation for coronavirus disease 2019 (COVID-19). Assay performance was assessed by percent agreement and Cohen’s kappa coefficient. Results Positive percent agreement with the SHC EUA reference assay was 82.8 % (95 % confidence interval (CI) 65.0 to 92.9) for Atila, 86.7 % (95 % CI 69.7 to 95.3) for the Altona E and S targets, and 86.7 % (95 % CI 69.7 to 95.3) and 90.0 % (95 % CI 73.6 to 97.3), for the CDC N1 and N2 targets, respectively. All assays demonstrated 100 % negative percent agreement. Kappa coefficients ranged from 0.86 to 0.92, indicating excellent agreement. Conclusions Performance was comparable among the SARS-CoV-2 nucleic acid amplification methods tested, with a limited number of discrepancies observed in specimens with low viral loads.